Analisis Dampak Rancangan Pekerjaan Terhadap Pertumbuhan Perusahaan - Roland Immanuel; Teguh Ainur Rohman; Wahyu Kristia Ningsih; Riska Nur Cahaya; Aurora Sheyra Nazwha Izzaty; Dewi Nuraini (STIKes Ibnu Sina Ajibarang, 2024)
A company is an entity that aims to achieve targets effectively and efficiently, where human resources (HR) play a crucial role as the main asset. For this reason, a job analysis is needed that includes an understanding of the responsibilities, authority and obligations of HR. From this analysis, companies can develop more specific job designs so that tasks can be carried out according to their respective skills and authority. The work design aims to explore topics related to the field of study, contribute to knowledge, and increase understanding of the topic being researched. This process involves qualitative research methods with a case study approach. Data was collected through in-depth interviews and document analysis, with a focus on in-depth analysis related to the topics studied. The job design includes strategic planning stages, developing new products and services, as well as increasing HR competency and productivity. SWOT analysis is used to identify a company's strengths, weaknesses, opportunities and threats in the market. Based on the results of the analysis, the company formulates an innovation strategy in products, processes and marketing. Human resource development is a top priority, including training, career development, and creating a work environment that supports creativity. HR management is also supported by a digital-based performance management system to increase organizational efficiency. Performance evaluations are carried out periodically to assess the effectiveness of strategy implementation and adjust necessary steps. This approach aims to achieve sustainable growth and strengthen the company's competitiveness in the global market.